Дослідження технологій безпровідного зв’язку в інтернеті речей: переваги, обмеження та потенційні загрози - Стрименешенко, О. С. (ХНУРЕ, 2024)
The Internet of Things (IoT) plays an important role in our modern lives, facilitating automation and convenience in many aspects of our daily and professional lives. One of the key aspects of the IoT is wireless communication, which allows devices to communicate with each other and with central servers without the need for physical connection via cables. In this article, we will explore the benefits, limitations, and potential threats of wireless communication in the IoT.
Keywords: безпровідний зв’язок; Internet of Things (IoT)